Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1002/bip.20363
|View full text |Cite
|
Sign up to set email alerts
|

NMR studies on self‐complementary oligonucleotides conjugated with methylene blue

Abstract: A carboxyl-functionalized methylene blue (MB) derivative was synthesized and covalently coupled to three CG-rich self-complementary 2'-deoxyoligonucleotides at their 5'-end. Thermodynamic and structural details about the interactions between the dye and oligonucleotide duplexes were investigated employing ultraviolet (UV) melting and (1)H nuclear magnetic resonance (NMR) experiments. In contrast to previous findings on MB binding, no specific intercalation or binding in the minor or major groove of the double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Thus, given the same T•A•T tract located next to the tethered MB in all triplex conjugates, itis strongly suggested that methylene blue preferentially binds through outer stacking onto the T•A•T base triple at the triplex blunt end, a unique structural feature of Tb2-MB. Such a favored outer stacking of MB was previously also found for an MB-oligonucleotide conjugate upon formation of a duplex with a complementary single strand [20]. As expected, the high-temperature duplex-single strand transition is not influenced by covalent attachment of MB to the third strand, thus again indicating that no irreversible dye-induced degradation at the duplex overhang has occurred.…”
Section: Bimolecular Triplex With Shifted Duplex Overhangsupporting
confidence: 81%
See 2 more Smart Citations
“…Thus, given the same T•A•T tract located next to the tethered MB in all triplex conjugates, itis strongly suggested that methylene blue preferentially binds through outer stacking onto the T•A•T base triple at the triplex blunt end, a unique structural feature of Tb2-MB. Such a favored outer stacking of MB was previously also found for an MB-oligonucleotide conjugate upon formation of a duplex with a complementary single strand [20]. As expected, the high-temperature duplex-single strand transition is not influenced by covalent attachment of MB to the third strand, thus again indicating that no irreversible dye-induced degradation at the duplex overhang has occurred.…”
Section: Bimolecular Triplex With Shifted Duplex Overhangsupporting
confidence: 81%
“…These involved a trimolecular triplex and two bimolecular triplexes with a T4-loop linking complementary strand of the duplex target to possibly increase stabilities of the triple-helical constructs. The MB moiety was tethered to the triplex-forming third strand oligonucleotide by a moderately long flexible linker as described in detail previously [20,21]. This allows for unrestrained interactions in the vicinity of the dye attachment at the triplex 3′-end.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA short oligonucleotides of defined sequence are becoming widely used in studies on DNAdrug interactions [1][2][3][4][5] . Highly specific and enantioselective DNA-binding transition metal complexes constitute an interesting class of drugs exhibiting versatile properties that, due to the rigid coordination framework with possibilities to vary the three-dimensional structure could be tuned for specific tasks with respect to DNA structure and sequence composition [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…∆∆ and ΛΛ were synthesized as previously reported 18,19 . The reduced LD (LD r ) is obtained by dividing the LD by the absorbance of the corresponding isotropic sample (A iso ), which for an anisotropic uniaxial sample can be obtained as A iso = (A∥ +2A ⊥ )/3 28 , so that (2) For molecules with a uniaxial orientation distribution, as can be expected for DNA in PVA matrix since the films are thick (30 µm for dry film) compared to the helix diameter (2 nm), LD r is a product of an orientation factor S and an optical factor O. The uniaxial distribution is not due to the DNA but to the flow properties of the PVA "melt".…”
mentioning
confidence: 99%